Huyula sebagai Fondasi Aksiologis Akuntansi: Tinjauan Literatur Praktik Akuntansi Berbasis Gotong Royong - Susanty Ismail; Fityan Halid; Harun Blongkod (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Accounting practices cannot be separated from the social and cultural values of the communities in which they operate. In the context of Gorontalo society, the value of mutual cooperation, known as huyula, plays a significant role in shaping the management and accountability of resources. This study aims to synthesize the literature on accounting practices based on huyula and to position it as an axiological foundation of accounting. The study employs an integrative literature review method by analyzing scholarly articles that examine accounting practices grounded in local wisdom across various contexts. The reviewed literature covers accounting practices in wedding rituals, micro-enterprises, consignment arrangements, social organizations, and institutional budgeting. The findings indicate that huyula-based accounting practices recognize both monetary and non-monetary contributions, such as labor, time, and trust, as meaningful forms of value. Moreover, accountability in these practices is communal and relational rather than limited to formal financial reporting. This study concludes that huyula functions as an axiological foundation that directs accounting practices toward social solidarity, moral responsibility, and community sustainability. These findings contribute to the development of socio-cultural accounting by demonstrating that local values can serve as a conceptual basis for more contextual and socially just accounting practices.